Key Aspects of Legal Reforms in the New Uzbekistan - Mukhitdinova, F.A. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
The article analyzes the key aspects of legal reforms carried out under the leadership of the President of the Republic of Uzbekistan Shavkat Mirziyoyev. It examines the main directions of transformation in the country’s legal system, including the renewal of the Constitution, improvement of the judicial and legal sphere, introduction of digital technologies into court activities, and strengthening of mechanisms for the protection of human rights and freedoms. Particular attention is paid to the content of the constitutional reform of 2023, issues of ensuring judicial independence, and increasing the effectiveness of justice. Based on the analysis of current legislation, regulatory legal acts, and the practice of their implementation, the article reveals the results of ongoing reforms and their significance for the further development of the rule of law. It is concluded that the reforms being carried out are comprehensive and consistent in nature, contribute to strengthening the rule of law, improving the level of legal protection of citizens, and forming a modern system of public administration in the conditions of New Uzbekistan.